(untitled) (Texas Journal of Philology, Culture and History, 2024)
The evolution of ancient Chinese philosophy and culture is examined in this article. Additionally, a comparison analysis is conducted between the morality-based Confucianism and the legislation-based Legism, both of which greatly influenced the Chinese people’s worldview in ancient China